Jihadi Groups and State-Building: The Case of Boko Haram in Nigeria. Issue 1 (30th November 2016) - Ladbury, Sarah; Allamin, Hamsatu; Nagarajan, Chitra; Francis, Paul; Ukiwo, Ukoha
The following article considers the extent to which the Nigerian jihadi group, Jama'atu Ahlis Sunna Lidda'awati wal-Jihad (JAS), also known as Boko Haram, is transforming its model of governance from domination by violence and force to governance through civil administration and public support. Drawing on over four years of research and programming in north-east Nigeria, the authors consider three aspects of such a transformation: the development of institutions, the propagation of an ideology and programmes to win over the hearts and minds of the wider population, and the role assigned to women and girls. The article finds that JAS has established little in the way of a civilian administration in the areas that have come under its control. Likewise, the movement has apparently made no concerted effort to project a vision of a future society or concrete benefits of the envisaged caliphate that would generate a level of public support. Moreover, the brutal treatment of women and girls belies any attempt by the movement to promote a positive vision of the role of women, even as wives and mothers. In this, JAS is seen to differ from a number of other jihadi movements that have relatively sophisticated approaches to generating popular support and recruiting members. The article goes on to suggest a number of reasons for JAS's failure to move towards a polity that is more consensual and less dependent on violence, as well as its implications for those who would seek to restrain the expansion and ideological reach of jihadist groups. It concludes by offering suggestions of how the government can seize the opportunity presented by this lack of a state-building strategy, in order to show the people of north-east Nigeria that it can offer a better alternative.